2010
DOI: 10.1242/dev.046995
|View full text |Cite
|
Sign up to set email alerts
|

Axonal projections of mechanoreceptive dorsal root ganglion neurons depend on Ret

Abstract: SUMMARYEstablishment of connectivity between peripheral and central organs is essential for sensory processing by dorsal root ganglion (DRG) neurons. Using Ret as a marker for mechanoreceptive DRG neurons, we show that both central and peripheral projections of mechanoreceptive neurons are severely impaired in the absence of Ret. Death of DRG neurons in Ret-deficient mice can be rescued by eliminating Bax, although their projections remain disrupted. Furthermore, ectopic expression of the Ret ligand neurturin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 54 publications
3
35
0
Order By: Relevance
“…The glabrous footpad, which receives dense cutaneous nociceptive and mechanoceptive sensory innervation, was examined using peripherin (Prph) and heavy chain neurofilament (NF-H) immunohistochemistry (Honma et al, 2010). Cutaneous sensory innervation of footpads was profoundly abnormal in Wnt1-cKO mice where Prph+ and NF-H+ axon innervation was reduced to 6.8% and 11.0%, respectively (n=2 or 3 mice and >40 tissue sections analyzed per genotype, P<0.0001, Student's t-test) (Fig.…”
Section: Generating Viable Elp1 Conditional Knockout Micementioning
confidence: 99%
“…The glabrous footpad, which receives dense cutaneous nociceptive and mechanoceptive sensory innervation, was examined using peripherin (Prph) and heavy chain neurofilament (NF-H) immunohistochemistry (Honma et al, 2010). Cutaneous sensory innervation of footpads was profoundly abnormal in Wnt1-cKO mice where Prph+ and NF-H+ axon innervation was reduced to 6.8% and 11.0%, respectively (n=2 or 3 mice and >40 tissue sections analyzed per genotype, P<0.0001, Student's t-test) (Fig.…”
Section: Generating Viable Elp1 Conditional Knockout Micementioning
confidence: 99%
“…In situ hybridization results showed that this was indeed the case. Because the expression of MafA, the early wave of Ret (Ret ϩ /TrkA Ϫ ), and Ret coreceptor GFR␣2 all can be used to indicate the development of the MafA ϩ / Ret ϩ /GFR␣2 ϩ LTMs (Bourane et al, 2009;Luo et al, 2009;Honma et al, 2010), we quantified the numbers of cells expressing GFR␣2, MafA, and early Ret (Ret ϩ /TrkA Ϫ ) in the DRG of control and c-Maf deletion mice at E18.5. We found that a reduction of 55%, 70%, and 50% in the number of GFR␣2 ϩ , MafA ϩ , and Ret ϩ /TrkA Ϫ DRG neurons occurred in c-Maf Ϫ/ Ϫ mice at E18.5 (Fig.…”
Section: Gfr␣2mentioning
confidence: 99%
“…Immunostaining of VGLUT1 was performed on spinal cord from c-Maf deletion mice and control mice. Because Ret expression in the laminae III/IV can be used for labeling MafA (Bourane et al, 2009;Luo et al, 2009;Honma et al, 2010), we performed immunostaining of Ret in c-Maf deletion mice as well. Immunostaining of TrkA and parvalbumin, the molecular markers for labeling projections of nociceptors and proprioceptors, was performed on spinal cord sections adjacent to those used for VGLUT1 staining.…”
Section: /Gfr␣2mentioning
confidence: 99%
See 2 more Smart Citations